Eleuthera and Brat Horin another look at Babatha’s Ketubba, P.Yadin 10 - Cotton, Hannah 1946- (2017)
P.Yadin 10, written between ad 124 and 128 in Aramaic, is the only Jewish ketubba to have survived from the Graeco-Roman period. It is all but identical to its ancient and modern counterparts, with the exception of the repetition in it of the puzzling phrase ‘as fitting the sustenance of a free woman’ (אנתה ברת-חורין), following the husband’s obligation to support his wife upon receipt of the dowry. The phrase, never attested either before or after in the history of the ketubba, is irreconcilable with the absence of any evidence for the existence of a difference between the marital rights of the female slave and the free woman. It is suggested that it may echo the Greek γυνὴ γαμετή in contemporary Greek marriage contracts, which once meant ‘legally free to marry’.